ArfX2 GTPase Regulates Trafficking From the Trans-Golgi to Lysosomes and Is Necessary for Liver Abscess Formation in the Protozoan Parasite Entamoeba histolytica - Saito-Nakano, Yumiko; Makiuchi, Takashi; Tochikura, Mami; Gilchrist, Carol A.; Petri, William A.; Nozaki, Tomoyoshi (Frontiers in Cellular and Infection Microbiology, 2021)
Entamoeba histolytica is the causative agent of amoebic dysentery and liver abscess in humans. The parasitic lifestyle and the virulence of the protist require elaborate biological processes, including vesicular traffic and stress management against a variety of reactive oxygen and nitrogen species produced by the host immune response. Although the mechanisms for intracellular traffic of representative virulence factors have been investigated at molecular levels, it remains poorly understood whether and how intracellular traffic is involved in the defense against reactive oxygen and nitrogen species. Here, we demonstrate that EhArfX2, one of the Arf family of GTPases known to be involved in the regulation of vesicular traffic, was identified by comparative transcriptomic analysis of two isogenic strains: an animal-passaged highly virulent HM-1:IMSS Cl6 and in vitro maintained attenuated avirulent strain. EhArfX2 was identified as one of the most highly upregulated genes in the highly virulent strain. EhArfX2 was localized to small vesicle-like structures and largely colocalized with the marker for the trans-Golgi network SNARE, EhYkt6, but neither with the endoplasmic reticulum (ER)-resident chaperon, EhBip, nor the cis-Golgi SNARE, EhSed5, and Golgi-luminal galactosyl transferase, EhGalT. Expression of the dominant-active mutant form of EhArfX2 caused an increase in the number of lysosomes, while expression of the dominant-negative mutant led to a defect in lysosome formation and cysteine protease transport to lysosomes. Expression of the dominant-negative mutant in the virulent E. histolytica strain caused a reduction of the size of liver abscesses in a hamster model. This defect in liver abscess formation was likely at least partially attributed to reduced resistance to nitrosative, but not oxidative stress in vitro. These results showed that the EhArfX2-mediated traffic is necessary for the nitrosative stress response and virulence in the host.